Modulation of gastrointestinal digestion of β-lactoglobulin and micellar casein following binding by (−)-epigallocatechin-3-gallate (EGCG) and green tea flavanols. Issue 7 (19th June 2020) - Dönmez, Özge; Mogol, Burçe Ataç; Gökmen, Vural; Tang, Ning; Andersen, Mogens Larsen; Chatterton, Dereck E. W.
Abstract : Milk proteins bind flavanoids (EGCG and green tea extract), affecting their in vitro digestibility and modulating flavanoid free radical scavenging. Abstract : The effect of binding of flavonoids, (−)-epigallocatechin-3-gallate (EGCG) and green tea extract (GTE), to beta-lactoglobulin (β-Lg) and micellar casein (micellar casein isolate, MCI) on protein digestibility was investigated. β-Lg resisted digestion by pepsin, but in the presence of EGCG the digestion of β-Lg was enhanced. Binding of EGCG to β-Lg was identified by nitro blue tetrazolium (NBT) staining and found, by isothermal titration calorimetry, to be an enthalpy-driven exothermic process, with a binding constant of 19 950 L mol −1 . Binding promoted a more rapid digestion of β-Lg during simulated upper duodenal digestion. NBT staining indicated a loss of binding of EGCG to β-Lg during combined gastric and distal small intestinal digestion and correlated with the cleavage of β-Lg. However, increased β-Lg heteromer formation and reduced β-Lg monomer digestibility were observed for the β-Lg-GTE complex. MCI was more digestible than β-Lg during pepsin digestion, but reduced digestibility was observed for both MCI-EGCG and MCI-GTE complexes, with loss of binding during intestinal digestion. The free radical scavenging capacity (FRSC) of EGCG remained stable for the β-Lg-EGCG complex throughout the gastric and intestinal phases of digestion, but this was significantly lowered for the MCI-EGCG complex. These results indicated that polyphenols bind to milk proteins modulating the in vitro digestibility and FRSC of β-Lg and MCI as a result of the formation of complexes.